Localization of basic and acidic argyrophilic proteins in nuclear structures of elongating mouse spermatids - Antalíková, L; Rozinek, J (Functional and developmental morphology, 1994)
Different cytochemical techniques at the electron microscopic level were used to investigate the presence of basic and acidic proteins during spermiogenesis in mice. Basic lysine rich proteins were demonstrated with an ethanolic solution of phosphotungstic acid, acidic agryrophilic proteins using two silver staining procedures applied en bloc and on the ultrathin lowicryl sections. Both types of proteins had very similar localization in the nucleoplasm and identical distribution within the postacrosomal dense lamina on the surface of late spermatid heads. The specificity of reactions is briefly discussed.
Keywords: Spermatids; kyseliny; myši; spermatidy; Silver Staining; Acids; Male; Alkalies; Animals; alkálie; jaderné proteiny; mužské pohlaví; Mice; Nuclear Proteins; zvířata; barvení stříbrem